Hierarchical carbon-coated FeP derived from FeOOH with enhanced sodium-storage performance. Issue 5 (9th February 2021) - Liu, Xiaofeng; Zhang, Wenbo; Zhong, Shaoyong; Zhang, Mengke; Tao, Shuo; Ma, Jianru; Li, Lizhi; Zhang, Wendi; Xie, Xiangyun; Zhang, Jianmin; Li, Dan
Abstract : As an energy-storage material, iron phosphide (FeP) has always been a research hotspot on account of its high theoretical capacity and low ion intercalation potential. However, its practical application is seriously limited by the structural damage and poor conductivity caused by the large volume expansion in the discharge process. In this work, the authors report a method combining hydrothermal synthesis with calcination to prepare a hollow sea-urchin-like FeP@C nanocomposite. The hollow sea-urchin-like structure can effectively alleviate volume expansion resulting from sodium (Na + )-ion intercalation. Carbon (C) coating not only limits the volume expansion and protects the integrity of the electrode structure but also improves electrical conductivity, promotes electron transmission, improves electrode reaction kinetics and thus improves the cycling performance of the FeP@C electrode. As an anode material of sodium-ion batteries, FeP@C showed good electrochemical performance with a capacity of 284.7 mAh/g after 200 cycles at a current density of 200 mA/g.